EFFECT OF WEED MANAGEMENT ON THE PERFORMANCE OF POTATO AND MICROFLORA POPULATION IN RHIZOSPHERE - Bera, Soumen; Poddar, Ratneswar; Ghosh, Ratikanta (Potato Journal, 2015)
To find out the effect of weed management on yield and quality of potato and microflora population in the rhizosphere, a field experiment was carried out at Bidhan Chandra Krishi Viswavidyalaya, Kalyani ( latitude: 22°57’E, longitude: 88°20’N and altitude: 9.75 m) during two consecutive rabi seasons (2009-10 and 2010-11). Among the different weed management treatments, oxyfluorfen 23.5% EC @ 400 g a.i./ha recorded minimum weed population as well as biomass. Potato tuber yield was maximum in weed free check (31.39 t/ha) which was at par with oxyfluorfen 23.5% EC @ 400 g a.i./ha (31.17 t/ha), oxyfluorfen 23.5% EC @ 300 g a.i./ha (29.605 t/ha) and oxyfluorfen 23.5% EC @ 200 g a.i./ha (29.29 t/ha). Similar trends were recorded in case of reducing sugar whereas reverse trends were observed in case of starch, protein and ascorbic acid content. No phytotoxic effect on potato plants was observed with any of the herbicidal treatment. Though herbicides decreased the micro-flora population initially but there was no detrimental effect in the long run.